Dental caries in the peruvian police population - Moreno-Quispe, Luz A.. (2018)
This article was developed thanks to the funding of Cienciactiva, an initiative of the National Council of Science, Technology and Technological Innovation (CONCYTEC). Contract No. 227-2015-FONDECYT. Thanks to the authorities and staff of PNP Huaraz Polyclinic for the support provided to the SERUMS staff to carry out this study (May 2012-May 2013). Thanks to the personnel of the company Innovation and Development for the support in the design of the study and the logistics and, to Rogelio Martínez Diez of the University of Valladolid-Spain for collaborating in the writing of the manuscript.